Comparative metaproteomic analysis on consecutively Rehmannia glutinosa-monocultured rhizosphere soil. - Linkun Wu; Haibin Wang; Zhixing Zhang; Rui Lin; Zhongyi Zhang; Wenxiong Lin (PLoS ONE, 2011)
BACKGROUND: The consecutive monoculture for most of medicinal plants, such as Rehmannia glutinosa, results in a significant reduction in the yield and quality. There is an urgent need to study for the sustainable development of Chinese herbaceous medicine. METHODOLOGY/PRINCIPAL FINDINGS: Comparative metaproteomics of rhizosphere soil was developed and used to analyze the underlying mechanism of the consecutive monoculture problems of R. glutinosa. The 2D-gel patterns of protein spots for the soil samples showed a strong matrix dependency. Among the spots, 103 spots with high resolution and repeatability were randomly selected and successfully identified by MALDI TOF-TOF MS for a rhizosphere soil metaproteomic profile analysis. These proteins originating from plants and microorganisms play important roles in nutrient cycles and energy flow in rhizospheric soil ecosystem. They function in protein, nucleotide and secondary metabolisms, signal transduction and resistance. Comparative metaproteomics analysis revealed 33 differentially expressed protein spots in rhizosphere soil in response to increasing years of monoculture. Among them, plant proteins related to carbon and nitrogen metabolism and stress response, were mostly up-regulated except a down-regulated protein (glutathione S-transferase) involving detoxification. The phenylalanine ammonia-lyase was believed to participate in the phenylpropanoid metabolism as shown with a considerable increase in total phenolic acid content with increasing years of monoculture. Microbial proteins related to protein metabolism and cell wall biosynthesis, were up-regulated except a down-regulated protein (geranylgeranyl pyrophosphate synthase) functioning in diterpenoid synthesis. The results suggest that the consecutive monoculture of R. glutinosa changes the soil microbial ecology due to the exudates accumulation, as a result, the nutrient cycles are affected, leading to the retardation of plant growth and development. CONCLUSIONS/SIGNIFICANCE: Our results demonstrated the interactions among plant, soil and microflora in the proteomic level are crucial for the productivity and quality of R. glutinosa in consecutive monoculture system.